2011
DOI: 10.1111/j.1743-6109.2011.02367.x
|View full text |Cite
|
Sign up to set email alerts
|

Practical Tips for Sexual Counseling and Psychotherapy in Premature Ejaculation

Abstract: Introduction A number of milestones in the treatment of premature ejaculation (PE) have occurred over the past five decades, including the development of various behavioral and cognitive techniques as well as pharmacotherapies that modify neurophysiological processes involved in ejaculation. Nevertheless, the notion that sexual responses such as PE are influenced by physiological, psychobehavioral, cultural, and relationship factors is as valid now as it was 50 years ago, and therefore, inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 28 publications
0
23
0
1
Order By: Relevance
“…plinarity (32,33): our data showed that group C, treated with the combination of pharmacotherapy and psychotherapy, was the one that improved the most in terms of results, as shown in Table 2. According to the results of our study, Group Psychotherapy appears to be effective in improving IELT, sexual satisfaction and anxiety both alone or in combination with Dapoxetine in treatment of PE.…”
Section: Discussionmentioning
confidence: 66%
“…plinarity (32,33): our data showed that group C, treated with the combination of pharmacotherapy and psychotherapy, was the one that improved the most in terms of results, as shown in Table 2. According to the results of our study, Group Psychotherapy appears to be effective in improving IELT, sexual satisfaction and anxiety both alone or in combination with Dapoxetine in treatment of PE.…”
Section: Discussionmentioning
confidence: 66%
“…PE'nin ortaya çıkması, alevlenmesi, devamı, bu dönemler-deki değişken aşırı tepkiler PE boyutunu çok daha yukarılara taşıyarak içinden çıkılmaz bir hâl almasına neden olmakta ve PE'ye yaklaşımı çok daha önemli kılmaktadır. 22 Primer PE'de PE süresinin 25±14 yıl, akkiz PE'de 5,6±4 yıl (p<0,01) olduğu gösterilmiştir. 8 Buna ek olarak daha ayrıntılı incelediğimizde, ça-lışmamızda da primer PE'de hasta yaşı arttıkça, yani PE'li geçen süre arttıkça aylık ilişki sayısında anlamlı bir azalma gözlenmiştir (p<0,01).…”
Section: Discussionunclassified
“…On the other hand, sexologic and behavioral techniques are considered the most efficacious care for restoration of desire within a couple and for the management of marital conflicts, PE, and the combination of medical and psychological treatments in PE (127). In this regard, a recent study demonstrated that sexual behavioral treatment combined with 30 mg of dapoxetine for 24 weeks had a higher efficacy than dapoxetine alone.…”
Section: Therapies For Pe Psychological Therapiesmentioning
confidence: 97%